Energy of the Surface Layer Deterioration of 1020 Steel and Copper at Dry Sliding against 1045 Steel with a High Electric Current Density; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Fadin V. V. (2016, 2016)
Title screen